Kam Alkış ve Kargışlarında Su Kültünün Karakteristiği. - MÜÇÜK KOTAN, Mehtap (Erdem)
The Turks, who regarded their natural environment as one of the fundamental elements for sustaining life, believed that every entity in nature possessed a soul and attributed sanctity to them. Human efforts to make sense of nature led to the meaningful interpretation of the four primary elements: earth, air, fire, and water. Among these, water gave rise to various practices and rituals. As one of the oldest fundamental cults in Turkish culture, water has been noteworthy since creation myths, appearing in numerous rituals with diverse forms. Water was ascribed different meanings in phenomena such as blessing, punishment, healing, protection, and purification. Consequently, feelings of reverence, fear, and hope toward water emerged within Turkish society, shaping behaviors. Water, as a shared symbol in Turkish communities, has been a vital element for sustaining life. At times, water served different purposes for people, symbolizing birth, death, or existence itself, leading to diverse forms of interaction between individuals, communities, and water. Due to its sacred nature, polluting water was forbidden, and those who committed such acts were believed to be punished by water spirits. Emerging as a common cultural motif in the Turkish world, water evoked various impacts in daily life. The water cult stood out with its qualities of abundance and prosperity, as well as its potential to cause illness. Therefore, it was deemed essential to avoid angering or displeasing the water spirit, as doing so was thought to have dire consequences. This duality highlights water’s sacred characteristics and its role in transitioning from chaos to cosmos, contributing to an orderly structure. Different narratives have provided the foundation for various beliefs related to water. Humans, seeking proximity to God, attributed divinity to the water cult, which subsequently served as a mediator between God and humankind. In these narratives, water embodies both sacred and divine attributes as well as destructive and punitive qualities. With both aspects, it has influenced societal life and human behavior through various practices. As one of the most significant elements in societal life, water frequently appears in Turkish oral narratives. Traces of the water cult are notably present in alkış and kargış, two such narratives. Sanctified water is used in the performance of alkış and kargış rituals conducted by kams or shamans. This study examines the role of water in kam alkış and kargış through selected examples from the Tuva, Altai-Teleut, Altai-Sayan, Uyghur, Kyrgyz-Kazakh, and Shor Turks. The study identifies the traits of water as depicted in these selected ritual texts and investigates how rituals associated with water have been reflected in alkış and kargış from past to present, highlighting the qualities through which water is emphasized.